Faktor Habitat Penentu pergerakan Gajah Sumatera di Taman Nasional Bukit Barisan Selatan - M. Latif Hadinata; Yanto Santosa; Burhanuddin Masy’ud (Jurnal Penelitian Pendidikan IPA, 2023)
Until now, conflicts between elephants and the community are still occurring, one of which is in the Bukit Barisan Selatan National Park. This conflict has a negative impact on both elephants and society, so it is necessary to examine the habitat factors that determine the movement of Sumatran elephants. Therefore, the aim of this study is to determine the daily movement of the elephants and to analyze the habitat factors that influence elephant movement. Data was collected in the form of elephant movements in one period which were obtained from the Bukit Barisan Selatan National Park. 1-year results obtained from the GPS stated that there are two groups of elephants, the citra elephant group and the bunga elephant group. The results showed that groups of elephants in Bukit Barisan Selatan National Park have lengths that ranged from 63 – 137 kilometers, with linear, zigzag and circular trajectories, and the frequency of points used is 2-6 repetitions with the time needed per-kilometers ranging from 110 – 518 minutes. Factors that influence elephant movement are track length, frequency of point used, time spent per-kilometers, altitude, slope, distance to settlements, distance to water sources, availability of feed, and availability of scrubbing trees